Commodity tail risks. Issue 2 (2nd October 2022) - Ammann, Manuel; Moerke, Mathis; Prokopczuk, Marcel; Würsig, Christoph Matthias
Abstract: In this study, we investigate the cross‐section of option‐implied tail risks in commodity markets. In contrast to findings from equity markets, left and right tail risks implied by option markets are both large. Commodity‐specific variables exert the largest influence on tail risk, while there is no evidence of systematic commodity factors that are linked to tail risk. Additionally, we find strong links to the equity markets, but also comovements to macroeconomic factors. Left or right tail risks are largely independent of variance risk premiums. Finally, both left and right tail risks are priced in the cross‐section of commodity futures returns.